The Use of Suspended Sediment Rating Curves In Malaysia Some Preliminary Considerations - Balamurugan, G (1989)
The suspended sediment rating curve technique is the most common method of estimating river suspended sediment loads in Malaysia. Thus, despite its crudeness, adherence to the correct Procedure of this technique is very imp0rtant. Three of the most common incorrect procedures in the suspended sediment rating curve technique were studied and compCl1ed to the results obtained from using correct procedures. Results of analysis showed that incorrect practices of this technique underestimate the annual suspended sediment load by more than 50 %. A correction factor to compensate for the use of non-continuous discharge data is also derived in this study